Disenchanted : the trials of Cinderella - Morrison, Megan, 1976- (Morrison, Megan, 1976- Tyme, 2016)
For generations the Charming men have been cursed, but now that the witch Envearia is dead the curse should be broken--however things are complicated at Charming Palace: King Clement is still nasty, Queen Maud has fled with the help of her son, Prince Dash, and Ella Coach (called Cinderella) would rather be at home sewing than living in the palace at Charming Prep school.